2018
DOI: 10.3389/fpsyg.2018.00947
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Cognitive-Motor Interference During Walking in Children: Does the Motor or the Cognitive Task Matter?

Abstract: The evidence supporting the effects of age on the ability to coordinate a motor and a cognitive task show inconsistent results in children and adolescents, where the Dual-Task Effects (DTE) – if computed at all – range from either being lower or comparable or higher in younger children than in older children, adolescents and adults. A feasible reason for the variability in such findings is the wide range of cognitive tasks (and to some extend of motor tasks) used to study Cognitive-Motor Interference (CMI). Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 98 publications
(146 reference statements)
1
21
1
2
Order By: Relevance
“…The hazard estimation process takes into account personal limitations and may impact the prioritization to a greater extent in the school‐aged children (Abbruzzese et al, 2014). Our results might confirm that healthy and CP children are able to exhibit healthy risk judgments (Schott and Klotzbier, 2018). In adults, the improvement of postural control could be attributed to a stiffening strategy (McNevin and Wulf, 2002) but we found less regular CoP fluctuations during dual‐tasking, suggesting higher degrees of freedom, a reduced attentional involvement in the postural regulation and thus greater automaticity while standing (Stins et al, 2011; Donker et al, 2007).…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…The hazard estimation process takes into account personal limitations and may impact the prioritization to a greater extent in the school‐aged children (Abbruzzese et al, 2014). Our results might confirm that healthy and CP children are able to exhibit healthy risk judgments (Schott and Klotzbier, 2018). In adults, the improvement of postural control could be attributed to a stiffening strategy (McNevin and Wulf, 2002) but we found less regular CoP fluctuations during dual‐tasking, suggesting higher degrees of freedom, a reduced attentional involvement in the postural regulation and thus greater automaticity while standing (Stins et al, 2011; Donker et al, 2007).…”
Section: Introductionsupporting
confidence: 83%
“…However, temporal and spatial parameters can still improve around 11–15 years, which can be explained by the continuing development of the nervous system and the changes of the anthropometric characteristics (Hausdorff et al, 1985). During childhood, some inconsistent results in dual‐task conditions have also been obtained in postural control (Ruffieux et al, 2015) and walking performances (Schott and Klotzbier, 2018; Saxena et al, 2017; Schaefer et al, 2015). (Olivier et al (2008)) showed an improvement of standing in children aged 4–11 years while watching a movie.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De modo que, el juego logró incentivar al estudiante, establecer patrones que le permite crear un pensamiento crítico y más flexible, esto ayudó al estudiante a llegar a una satisfacción significativa, el juego Plants vs. Zombies produjo efectos positivos en las tareas de procedimientos con conexiones, de manera que el estudiante encuentra un buen escenario, capta la atención y ayuda en el cambio de comportamientos convirtiendo así al juego en una herramienta positiva (Terrell, 2016;Jacobs, 2016). Para alcanzar el rendimiento académico se debe desarrollar tareas motoras con ciertos grados de dificultad, de manera que mientras más difícil sea la tarea, mayor será el beneficio para desarrollar tareas de procedimientos con conexiones (Schott & Klotzbier, 2018).…”
Section: Resultados Y Discusiónunclassified
“…Interrupting the consistency of moving the pedals within one event of use may be a result of changing to tasks that require more or less concentration or precision. Depending on the task, it may be easier or more difficult to integrate the movement of the legs, solving the task and maintaining a good performance (e.g., taking a phone call, copying a text or using the mouse) [ 54 , 55 , 56 ]. This task-dependence could also explain our findings of a maximum standard deviation of 24.5 rpm, resulting from different speeds of moving while solving changing tasks with different demands.…”
Section: Discussionmentioning
confidence: 99%